2021
DOI: 10.1002/pat.5311
|View full text |Cite
|
Sign up to set email alerts
|

Fast prepare exfoliated montmorillonite water suspension with assistance of melamine cyanurate and the superlattice obtained by self‐assembly

Abstract: To explore the exfoliation mechanism of montmorillonite (MMT) layers assisted by melamine cyanurate (MCA), the MCA crystal structures based on the concentration of raw materials and the preparation of MMT‐MCA superlattice are investigated. Here, the correlation between MCA crystal growth and concentration of cyanuric acid (CA) and melamine (MA) water solutions on glass substrate are analyzed using XRD and SEM. With the increasing of concentration of CA and MA water solutions, the stacking of MCA layers along [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…[ 34 ] An additional characteristic diffraction peak at 2 θ = 27.6° was observed in the spectrum of Lyocell‐MCA fiber, which is attributed to the characteristic peak of the flame retardant itself owing to the large content of the flame retardant in the fiber. [ 35 ] Peak fitting of the spectra in Figure 3 revealed that the crystallinity of non‐modified Lyocell, Lyocell‐MPP, and Lyocell‐MCA fibers was 58.5%, 52.8%, and 51.6%, respectively. The lower crystallinity displayed by the flame‐retardant fibers was attributed to the introduction of the flame retardants, which hindered the movement of the cellulose molecular chains and grain growth.…”
Section: Resultsmentioning
confidence: 99%
“…[ 34 ] An additional characteristic diffraction peak at 2 θ = 27.6° was observed in the spectrum of Lyocell‐MCA fiber, which is attributed to the characteristic peak of the flame retardant itself owing to the large content of the flame retardant in the fiber. [ 35 ] Peak fitting of the spectra in Figure 3 revealed that the crystallinity of non‐modified Lyocell, Lyocell‐MPP, and Lyocell‐MCA fibers was 58.5%, 52.8%, and 51.6%, respectively. The lower crystallinity displayed by the flame‐retardant fibers was attributed to the introduction of the flame retardants, which hindered the movement of the cellulose molecular chains and grain growth.…”
Section: Resultsmentioning
confidence: 99%